DESIGN OF FASHION CLOTHING ON THE BASISOF PARAMETRIC DESIGN PRINCIPLES - Колосніченко, М. В.; Чупріна, Н. В.; Кротова, Т. Ф.; Олішевська, Т. М. (Art and Design, 2020)
The purpose of this article is to define and characterize design and composite solutions of objects of parametric design, their adaptation to the formation of tectonic structure of clothing models and the development of a fashionable costume collection.In the study of basic concepts of parametric design, a comparative analysis was conducted, visual-graphic means of artistic and stylistic generalization and interpretation in various fields ofdesign and architecture were applied.The analysis of collections of designer brands’ clothing was carried out by using composite analysis and method of systems design. The system-structural approach and graphical modeling of the form were applied to determine the conceptual decisions, to form the project image of the costume collection and to develop clothing models. The principles and peculiarities of shaping in parametric design, as well as the means of their implementation in the objects of architecture, sculpture, in the design of costume and accessories, are investigated. The development of parametric design in the formation of actual models of clothing, taking into account world trends in the modern market is investigated in the paper. The design and compositional means and structural elements of the parametric design in the project image creating and the development of the clothing collection are characterized. Theoretical substantiation of artistic and stylistic modifications of the project image with the use of parametric elements of forms determined the ways of their transfer and transformation in the development of fashionable clothing of mass demand. Based on the analysis of the creativity of fashion designers in this area, the relevance of the costume design on the basis of parametric characteristics of architectural objects has been revealed. It describes 3D printing tools, sophisticated articulation and repetition of form elements as the guiding principles of parametric design embodied in clothing design. The study for the first time comprehensively considered the means of adapting the features of parametric design objects in the formation of tectonic structure of actual costume models.